2016
DOI: 10.1007/s11102-016-0780-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-pituitary antibodies against corticotrophs in IgG4-related hypophysitis

Abstract: Our study suggests that autoimmunity is involved in the pathogenesis of IgG4-RH and that corticotrophs are the main antigenic target, highlighting a possible new diagnostic marker for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Recent studies have also shown that prevalence of IgG4-related hypophysistis has been underestimated [43,44]. Αutoimmunity seems to be involved in the pathogenesis of IgG4 hypophysitis and corticotrophs are the main antigenic target [44]. Glucocorticoid therapy is generally effective although rare cases refractory to glucocorticoids remitted with rituximab treatment as in our case [45].…”
Section: Treatment/patients Characteristicsmentioning
confidence: 60%
See 1 more Smart Citation
“…Recent studies have also shown that prevalence of IgG4-related hypophysistis has been underestimated [43,44]. Αutoimmunity seems to be involved in the pathogenesis of IgG4 hypophysitis and corticotrophs are the main antigenic target [44]. Glucocorticoid therapy is generally effective although rare cases refractory to glucocorticoids remitted with rituximab treatment as in our case [45].…”
Section: Treatment/patients Characteristicsmentioning
confidence: 60%
“…Although the precise mechanisms remain unclear, hypophysitis is associated with the detection of antithyrotroph, anticorticotroph, and antigonad-otroph antibodies [41,42]. Recent studies have also shown that prevalence of IgG4-related hypophysistis has been underestimated [43,44]. Αutoimmunity seems to be involved in the pathogenesis of IgG4 hypophysitis and corticotrophs are the main antigenic target [44].…”
Section: Treatment/patients Characteristicsmentioning
confidence: 99%
“…Although the prevalence of IgG4-related hypophysitis remains unknown, a study of 170 consecutive outpatients with hypopituitarism and/or central diabetes insipidus reported that IgG4related hypophysitis was detected in 30% (7 of 23) of hypophysitis cases and 4% of all cases (7 of 170), suggesting that IgG4-related hypophysitis is not so rare [18]. Although the roles of IgG4 in hypophysitis remain unknown, autoantigen candidates (growth hormone and proopiomelanocortin) [19] and the presence of antipituitary antibodies [20] have been reported in patients with biopsy-proven IgG4-related hypophysitis, suggesting that autoimmunity is involved, at least in part, in the pathogenesis of IgG4-related disease [15]. Anterior pituitary dysfunction and/or central diabetes insipidus accompanied by enlargement of the pituitary gland and/or thickened stalk are often observed in patients with IgG4related hypophysitis [16].…”
Section: Igg4-related Hypophysitismentioning
confidence: 99%
“…In IgG4H, anterior pituitary deficiency and DI develop in 48% [59]. Patient history and clinical presentation are useful tools in differentiating IgG4H from LH [1, 60]. IgG4-RD can cause panhypopituitarism, anterior hypopituitarism, or isolated DI in 50, 25, and 18% of cases, respectively [61, 62].…”
Section: Resultsmentioning
confidence: 99%